2005
DOI: 10.1097/01.alc.0000158934.50534.b7
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stimulation Reward Performance and Sucrose Maintained Behaviors in Alcohol-Preferring and -Nonpreferring Rats

Abstract: The results demonstrate that responding for BSR is not associated with EtOH preference, insofar as alcohol-preferring and -nonpreferring rats respond similarly under an array of reinforcement schedules and current intensities. In contrast, genetic selection for EtOH preference is highly associated with responding for a palatable sucrose reward, and the relation increases as the reward cost for the sucrose increases. These findings suggest that similar/overlapping mechanisms of action regulate the reinforcing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Over a range of sucrose concentrations, P rats self-administered more sucrose than NP rats. This finding is consistent with previous studies in which it was found that the P rats consume greater amounts of sucrose (Stewart et al, 1994;Eiler et al, 2005). Our data for sucrose self-administration are also consistent with results from human studies on the association between alcoholism and sucrose palatability and preference (Kampov-Polevoy et al, 1997, 2003.…”
Section: Sucrose-and Cocaine-taking Behavior In P and Np Ratssupporting
confidence: 93%
See 1 more Smart Citation
“…Over a range of sucrose concentrations, P rats self-administered more sucrose than NP rats. This finding is consistent with previous studies in which it was found that the P rats consume greater amounts of sucrose (Stewart et al, 1994;Eiler et al, 2005). Our data for sucrose self-administration are also consistent with results from human studies on the association between alcoholism and sucrose palatability and preference (Kampov-Polevoy et al, 1997, 2003.…”
Section: Sucrose-and Cocaine-taking Behavior In P and Np Ratssupporting
confidence: 93%
“…Finally, the findings on the lack of P-NP differences in cocaine self-administration are consistent with those of Eiler et al (2005), who reported lack of P-NP differences for medial forebrain bundle stimulation threshold, an established measure of reward sensitivity (Wise, 1996). The findings of the lack of P-NP differences in cocaine self-administration and brain stimulation reward indicate that P-NP differences in nicotine-taking behavior are not the result of general reward deficits in NP rats.…”
Section: Sucrose-and Cocaine-taking Behavior In P and Np Ratssupporting
confidence: 84%
“…Interestingly, in animal studies, rats that are bred for high sweet consumption also administer more alcohol (Dess et al 1998(Dess et al , 2005 and other drugs (Carroll et al 2002(Carroll et al , 2007 than less sweet consuming rats. The opposite is also true; that is, rats with high alcohol consumption also display an increased preference for sweets compared with low alcohol-consuming animals (Eiler et al 2005;Grahame et al 1999;Stewart et al 1994). These results support the hypothesis that sweet consumption and substance use may be closely genetically related.…”
Section: Introductionmentioning
confidence: 70%
“…This is likely due to the insensitivity of the home-cage paradigm (Roberts et al, 2000). It is well documented that a high correlation exists between intake of EtOH and sweet solutions in the P and HAD rats (Murphy et al, 2002;Woods et al, 2003;Eiler et al, 2005). However, it is important to note that as with the P rats (Stewart et al, 1994), the a1 (À/À) mice did not show an oral preference for bitter tasting solutions (Blednov et al, 2003b); hence, the link between EtOH and reinforcement for sweet palatable solutions in both a1-null mutants and P rats was reinforcer specific.…”
Section: Discussionmentioning
confidence: 99%